Pengaruh Green Accounting dan Kinerja Lingkungan Terhadap Kinerja Keuangan Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Lestari, Whidy Bintang; Hadisantoso, Erwin; Asni, Nur (VALUE, 2025)
The purpose of the following study is to examine the influence of green accounting and environmental performance on the financial performance of mining companies listed on the IDX, a very important urgency given the significant environmental impact of the mining industry and the need for sustainable business practices. Data was obtained from the company's financial statements and sustainability reports for the 2021-2023 period. Green accounting measurement through environmental costs, while environmental performance measurement through PROPER. The analysis was applied by the panel data regression method through the help of the E-Views application 12. The study's findings show that green accounting positively affects financial performance, which means that the higher the environmental costs incurred, the better the company's financial performance. Environmental performance also positively affects financial performance, which indicates that companies with high PROPER ratings have a greater chance of increasing profitability. Companies that meet stakeholder expectations regarding environmental responsibility will receive greater support, including from investors and customers. Thus, the implementation of green accounting and improving environmental performance not only strengthens the company's competitiveness and reputation, but also creates long-term financial and sustainability benefits, making a significant contribution to companies and stakeholders in increasing awareness and implementation of responsible environmental practices.